Hubungan Komunikasi Terapeutik Perawat Dengan Tingkat Kepuasan Pasien Rawat Inap Rumah Sakit Islam Purwokerto - Sari, Elina Puspita; Etlidawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: Hospitals are one of the subsystems of healthcare services that provide two main types of public services: healthcare and administrative services. Healthcare services include medical assistance, medical support services, medical rehabilitation, and nursing care. Effective communication techniques are essential in delivering these services, especially by nurses. Communication is the foundation of all human interaction. Objective: This study aims to examine the correlation between nurses' therapeutic communication and the level of satisfaction among inpatients at Rumah Sakit Islam Purwokerto. Methods: This research employed a cross-sectional design. A total of 89 inpatients who met the inclusion criteria were selected using proportional stratified random sampling.Data were collected using a questionnaire. Results: Spearman rank correlation analysis between therapeutic communication and patient satisfaction showed a correlation coefficient (r) of 0.333 with a significance level of p =0.001 (p 0.05). Conclusion: Based on the data analysis, it can be concluded that there is a significant correlation between nurses' therapeutic communication and inpatient satisfaction at Rumah Sakit Islam Purwokerto.